2011
DOI: 10.1159/000325225
|View full text |Cite
|
Sign up to set email alerts
|

The Application of Vagus Nerve Stimulation and Deep Brain Stimulation in Depression

Abstract: Despite the progress in the pharmacotherapy of depression, there is a substantial proportion of treatment-resistant patients. Recently, reversible invasive stimulation methods, i.e. vagus nerve stimulation (VNS) and deep brain stimulation (DBS), have been introduced into the management of treatment-resistant depression (TRD). VNS has already received regulatory approval for TRD. This paper reviews the available clinical evidence and neurobiology of VNS and DBS in TRD. The principle of VNS is a stimulation of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0
4

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(31 citation statements)
references
References 145 publications
(104 reference statements)
1
26
0
4
Order By: Relevance
“…Electric stimulation provides direct modulatory effects in subcortical sites, i.e, there are changes in cortical excitability. Neuroimaging studies corroborate these effects, showing neuronal activity changes in certain sites of brain, such as the amygdala, insula, precentral gyrus, hippocampus, and thalamus 4,5,16,21 . These neuroanatomical connections have been linked to the "bottom-up" mechanism of modulation by CNS 9 .…”
Section: The "Bottom-up"mechanismmentioning
confidence: 73%
See 1 more Smart Citation
“…Electric stimulation provides direct modulatory effects in subcortical sites, i.e, there are changes in cortical excitability. Neuroimaging studies corroborate these effects, showing neuronal activity changes in certain sites of brain, such as the amygdala, insula, precentral gyrus, hippocampus, and thalamus 4,5,16,21 . These neuroanatomical connections have been linked to the "bottom-up" mechanism of modulation by CNS 9 .…”
Section: The "Bottom-up"mechanismmentioning
confidence: 73%
“…Different nonpharmacological brain stimulation techniques have been used in clinical neurology and psychiatry, such as electroconvulsive therapy (ECT), repetitive transcranial magnetic stimulation (rTMS), vagus nerve stimulation (VNS), transcranial direct current stimulation (tDCS), deep brain stimulation (DBS), stereotactic surgery and trigeminal nerve stimulation (TNS) 1,2,3,4,5 . Theoretically, such techniques present different mechanisms of action.…”
mentioning
confidence: 99%
“…The nerve delivers input to the forebrain via the parabrachial nucleus and locus ceruleus, which connect to central structures in the limbic system, such as the amygdala and hypothalamus [86]. Vagal nerve stimulation (VNS) has been explored with increasing reports of long-term success in the treatment for refractory depression [87]. Research has demonstrated VNS has a role in increasing serotonergic and noradrenergic activity in the brain with evidence that it increases perfusion of limbic structures [88,89].…”
Section: Future Potential Psychosurgical Indications and Targetsmentioning
confidence: 99%
“…These methods are not adequately evaluated in the treatment of bipolar depression or for comparative effi cacy between unipolar and bipolar depression. They are reviewed elsewhere [ 124,128,167,168,191,207,225,242 ] .…”
Section: Short-term Treatment: Bipolar Depression and Mixed Statesmentioning
confidence: 99%